6t-2,t=5

Simple and best practice solution for 6t-2,t=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-2,t=5 equation:



6t-2.t=5
We move all terms to the left:
6t-2.t-(5)=0
We add all the numbers together, and all the variables
4t-5=0
We move all terms containing t to the left, all other terms to the right
4t=5
t=5/4
t=1+1/4

See similar equations:

| 4x^-5x+1=0 | | 5(x−1)+3x=19 | | -72=8-6(6m+7) | | x=320/5x | | -3x=-8.4 | | -72=8-6(6m+7 | | 24=∣4a−4∣ | | 4|x-2|-1=7 | | 76=-2t | | 13x+30=160 | | (-5/7)m=10/21 | | -3+n/7=-2 | | (5x-3(4x-8)=-11 | | 24=  ∣4a−4∣ | | -0.25v=-2.25 | | 68x+100=440 | | n/3+3=9 | | 24=  ∣4a−4∣∣4a−4∣ | | 1+2(x+4)+7=-4 | | 100x+68=440 | | 6.6c+2=4c-1.7 | | 165+2x÷3=180 | | 38=t–4 | | 68x100=440 | | x^2-24x+224=0 | | 60=125t | | 3k-kk=12 | | 4z+8=56 | | 9/10w=5/12 | | -4x-16=-4x+16 | | -5v+12+9=4v+42 | | 2(2x+1)+3(x+2)=22 |

Equations solver categories